DAYA TERIMA PROPORSI KACANG HIJAU (PHASEOLUS RADIATA L) DAN BEKATUL (RICE BRAN) TERHADAP KANDUNGAN SERAT PADA SNACK BAR - Pricilya, Vyatri; Wirjatmadi, Bambang; Andriani, Merryana (Media Gizi Indonesia, 2017)
Snack bar is a product made from cereal and nuts that usually consumed between meals. Commercial snack bar contains energy, protein, and ï¬ber. The ï¬ber content in it is usually 1 gram per 25 grams serving. The ï¬ber content is relatively low because food categorized as high ï¬ ber if it has 5 grams per 100 gram products. Therefore, a new innovation to improve its ï¬ ber content is required. Green bean and rice bran are type of food with high ï¬ber content that possible to be added in snack bar. The purpose of this research was to determine the acceptability and ï¬ ber content in snack bar. This was true experimental research with complete random design (CRD) with 5 treatments. Organoleptic test to assess acceptability of the snack bar was done by 5 trained panelists and 30 non trained panelists. Fiber content was calculated using Indonesia Food Composition Database and also analyzed by proximate test in laboratory. The result showed that formula 3 had the highest score than other formulas. Laboratory result showed ï¬ ber content in formula 3 was 1.98 grams per 25 grams snack bar. The conclusion of this research is the snack bar with proportion of green beans and rice bran has a good acceptability and higher ï¬ ber content compared to commercial snack bar. Keywords: ï¬ ber, green beans, rice bran, snack bar